CRISPR/Cas9 knockout of USP18 enhances type I IFN responsiveness and restricts HIV‐1 infection in macrophages. Issue 6 (13th February 2018) - Taylor, Jared P.; Cash, Melanie N.; Santostefano, Katherine E.; Nakanishi, Mahito; Terada, Naohiro; Wallet, Mark A.
Abstract: The IFN‐stimulated gene ubiquitin‐specific proteinase 18 ( USP18 ) encodes a protein that negatively regulates T1 IFN signaling via stearic inhibition of JAK1 recruitment to the IFN‐α receptor 2 subunit (IFNAR2). Here, we demonstrate that USP18 expression is induced by HIV‐1 in a T1 IFN‐dependent manner. Experimental depletion of USP18 by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) gene editing results in a significant restriction of HIV‐1 replication in an induced pluripotent stem cell (iPSC)‐derived macrophage model. In the absence of USP18, macrophages have increased responsiveness to stimulation with T1 IFNs with prolonged phosphorylation of STAT1 and STAT2 and increased expression of IFN‐stimulated genes that are key for antiviral responses. Interestingly, HIV‐1 requires some signaling through the T1 IFN receptor to replicate efficiently because a neutralizing antibody that inhibits T1 IFN activity reduces HIV‐1 replication rate in monocyte‐derived macrophages. USP18 induction by HIV‐1 tunes the IFN response to optimal levels allowing for efficient transcription from the HIV‐1 LTR promoter while minimizing the T1 IFN‐induced antiviral response that would otherwise restrict viral replication and spread. Finally, iPSC and CRISPR/Cas9 gene targeting offer a powerful tool to study host factors that regulate innate immune responses. Abstract : USP18 promotes HIV‐1 replication by negatively regulating expression of antiviral genes induced by T1 IFN signaling.